A PANS Method Based on Rotation-Corrected Energy Spectrum for Efficient Simulation of Rotating Flow - Liu, Benqing; Yang, Wei; Liu, Zhuqing (Frontiers in Energy Research, 2022)
A partially-averaged Navier-Stokes method with a new expression of fk based on the rotation-corrected energy spectrum is proposed. It is coupled with the shear-stress transport (SST) turbulence model to simulate two typical rotating flows that are rotating channel flow and flow in a centrifugal pump impeller. The results of two traditional energy spectrum-based fk expressions (ES1 and ES2), and DNS/experimental results, are used for comparison. The results show that the fk distribution predicted based on the rotation-corrected energy spectrum is more reasonable in both near-wall areas and mainstream. In the region with turbulence enhanced and more turbulence scales exist such as the pressure side in the rotating channel flow the fk value is low and more turbulence scales is resolved. While in the region with turbulence suppressed and less turbulence scales exist such as the suction side the fk value is relatively high. The model with new fk expression can produce better results since it can give a more reasonable fk distribution. At the same time the new model is more efficient since it shows better calculation performance with the same mesh scale and low cost with a comparable calculation performance.